Gender equality at work : some are more equal than others - Ramparsad, Nitasha (Knowledge Resources KR, 2019)
"This book shows how to circumvent many of the barriers to implementing gender mainstreaming. You⁰́₉ll also learn how to create a more enabling environment at work for gender equality initiatives, as well as how to get senior management buy-in, implement company gender policies and practical corporate guidelines, develop a gender equality action plan, operationalise gender equality, implement sustainable gender equality campaigns and more."--Publisher's description.